2012
DOI: 10.5923/j.mechanics.20120205.04
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibration Analysis of Circular Cylindrical Shells: Comparison of Different Shell Theories

Abstract: In order to study the free vib ration of simply supported circular cy lindrical shells, a semi-analytical p rocedure is discussed in detail. In this technique, beam function is used as an approximat ion for simp ly supported boundary conditions. A literature review reveals that beam functions are used extensively in predicting natural frequencies of shells. Since this method does not involve with boundary condition equations, there is no need to deal with intense calculations. Hence, it is important to check t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…However, in a paper by Farshidianfar, it was shown that the Soedel theory provides better results when compared to other theories considered. 24 Hence, in this paper, Soedel's shell theory for a thin-walled, simply supported, cylindrical shell is used to model the response of the shell due to a point excitation. 25 The resulting normal component of displacement is incorporated into Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, in a paper by Farshidianfar, it was shown that the Soedel theory provides better results when compared to other theories considered. 24 Hence, in this paper, Soedel's shell theory for a thin-walled, simply supported, cylindrical shell is used to model the response of the shell due to a point excitation. 25 The resulting normal component of displacement is incorporated into Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
“… óêàçàííîé ëèòåðàòóðå áîëüøîå âíèìàíèå óäåëÿåòñÿ îáîëî÷êàì âðàùåíèÿ, â ÷àñòíîñòè öèëèíäðè÷åñêèì. Ðÿä ðåçóëüòàòîâ ðåøåíèé äëÿ öèëèíäðè÷åñêèõ îáîëî÷åê, â òîì ÷èñëå è âçàèìîäåéñòâóþùèõ ñî ñðåäîé, ïðåäñòàâëåí â ñòàòüÿõ è ìàòåðèàëàõ äèññåðòàöèé [13][14][15][16][17][18][19][20][21][22][23]. Ñëåäóåò îòìåòèòü, ÷òî â ëèòåðàòóðå ìàëî âíèìàíèÿ óäåëÿåòñÿ îáîëî÷êàì êîíå÷íûõ ðàçìåðîâ è ñðàâíèòåëüíîìó àíàëèçó ðåçóëüòàòîâ àíàëèòè÷åñêèõ è ÷èñëåííûõ ðåøåíèé, â ÷àñòíîñòè, ñ èñïîëüçîâàíèåì ìåòîäà êîíå÷íûõ ýëåìåíòîâ.…”
Section: ââåäåíèåunclassified
“…They reported that some theories such as Love-Timoshenko, Arnold-Warburton, Flugge Byrne-Lur'ye, Reissner-Naghdi-Berry, Sanders, Vlasov, and Soedel produce the same results with respect to predicting the natural frequencies and mode shapes of the shell. Based on experimental data, they also stated that Soedel's model was one of the theories that provided more accurate results than some of the other theories and suggested that the Donnell-Mushtari theory is not as precise as other theories [77].…”
Section: Structural Behaviormentioning
confidence: 99%